2017
DOI: 10.1080/10498850.2016.1251521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Concentration and Extremely Halophilic Archaea on the Safety and Quality Characteristics of Traditional Salted Anchovies

Abstract: Extremely halophilic archaea (EHA) might play an important role in salted fish production. So far, limited information has been available on the effect of EHA and salt concentration on the safety and quality characteristics of salted anchovies. Eight Halobacterium salinarum strains were isolated from different sea salt samples and subjected to phenotypic and genotypic characterization. The strains were then inoculated into fresh salt before addition to anchovies. A total of 18 experimental productions were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The levels of the microbial groups investigated in this study are comparable to those reported in literature (Alfonzo et al, 2017a;Aponte et al, 2010;Hern andez-Herrero et al, 1999b). In the present study, a decrease of the microbial counts of total aerobic mesophilic microorganisms, LAB (cocci and rods), Enterobacteriaceae and Staphylococcaceae was observed in relation to the type of salt applied for the salting process.…”
Section: Microbiological Countssupporting
confidence: 90%
See 3 more Smart Citations
“…The levels of the microbial groups investigated in this study are comparable to those reported in literature (Alfonzo et al, 2017a;Aponte et al, 2010;Hern andez-Herrero et al, 1999b). In the present study, a decrease of the microbial counts of total aerobic mesophilic microorganisms, LAB (cocci and rods), Enterobacteriaceae and Staphylococcaceae was observed in relation to the type of salt applied for the salting process.…”
Section: Microbiological Countssupporting
confidence: 90%
“…In the present study, a decrease of the microbial counts of total aerobic mesophilic microorganisms, LAB (cocci and rods), Enterobacteriaceae and Staphylococcaceae was observed in relation to the type of salt applied for the salting process. This trend was not followed by the halophilic populations, since the salty environment became selective for this microbial group (Alfonzo et al, 2017a;Aponte et al, 2010;Czerner & Yeannes, 2014;Pons-Sanchez-Cascado et al, 2005).…”
Section: Microbiological Countsmentioning
confidence: 93%
See 2 more Smart Citations
“…The input matrix used for HCA consisted of chemical compounds and MIC for both E. coli and S. enterica. The PCA explored the input matrix based on the 9 EOs introduced as cases and the normalized average data of 178 chemical compounds grouped according to their chemical classes and MIC for both E. coli and S. enterica considered as explanatory variables, preliminary evaluated by using the Barlett's sphericity test (Alfonzo et al, 2017;Bautista Gallego et al, 2011). Eigenvalues were calculated and score and loading plots including both EOs samples and GC-MS constituents were generated (Torregiani et al, 2017).…”
Section: Statistical and Explorative Multivariate Analysesmentioning
confidence: 99%